Merekonstruksi Paradigma Pembangunan: Batasan dan Relevansi Teori Pembangunan Konvensional di Masyarakat Mayoritas Muslim - Vathimatuz Zahroh; M.F. Hidayatullah (PT Maju Malaqbi Makkarana, 2026)
Conventional development theory has become the dominant paradigm in the formulation of development policies in various developing countries, including Muslim-majority countries. However, its orientation, which focuses on economic growth, industrialization, and capital accumulation, is often considered incapable of addressing issues of social inequality, distributive justice, and the need for development that aligns with religious values. This study aims to analyze the relevance and limitations of conventional development theory in the context of Muslim-majority societies and to formulate a direction for reconstructing a development paradigm that is more in line with Islamic economic principles. The study used a qualitative approach with library research methods. Data were obtained from various literature sources, including books, journal articles, and scientific works related to development theory, Islamic economics, modernization, dependency, and economic growth. The analysis was conducted through a theoretical synthesis of various relevant perspectives. The results show that conventional development theory, particularly modernization theory, dependency theory, and neoclassical growth theory, still retains relevance in explaining the processes of economic transformation, industrialization, human resource development, and the importance of technological innovation. However, these theories have limitations because they tend to be based on secular and materialistic paradigms that ignore spiritual, moral, and social justice dimensions. From an Islamic perspective, development aims not only to achieve economic growth but also to realize holistic well-being (falah) through a balance between material and spiritual aspects. This study concludes that a reconstruction of the development paradigm is necessary through the integration of Islamic values ​​into a modern development framework to produce development that is inclusive, just, sustainable, and oriented towards the overall well-being of humanity.